PERANCANGAN ASRAMA MAHASISWA TOJO UNA-UNA DI GORONTALO DENGAN PENDEKATAN ARSITEKTUR HYBRID - Feldiansyah A Akili; Bakhtiar; Ari Putra Rachman; Novita Shamin (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2025)
This study aims to design a student dormitory in Tojo Una-Una, Gorontalo, that meets the needs and reflects the unique identity of the Tojo Una-Una region through a hybrid architectural approach. The method used is systematic design with data collection through field surveys, interviews with managers, and analysis of the physical and environmental conditions of the site. The design process is dynamic, using a feedback method to adjust the design to changes that occur. The results of the study show that the current student dormitory is still in the form of rented houses with inefficient infrastructure management. This has an impact on the quality of the site environment, such as limited land, inadequate space, chaotic access, and a lack of supporting facilities such as parking lots and canteens. These conditions have led many students from Tojo Una-Una to prefer living in rented rooms or public housing. Therefore, the dormitory design developed in this study is expected to provide a concrete solution to these issues while contributing significantly to the development of architectural theory and practice, particularly in the context of designing functional student housing facilities rooted in local values in the city of Gorontalo.